Public Danger of Corruption Crimes in the Sphere of Housing and Communal Services - S. I. Kel'm (Сибирское юридическое обозрение, 2020)
Currently, housing and communal services as a specific form of socio-economic relations are most susceptible to criminal influence. The Author of the article examines corruption crimes in the field of housing and communal services (HCS) from the point of view of public danger. Corruption as a social and legal phenomenon continues to be a dangerous factor in the development of the housing and utilities sector. The article draws attention to the systemic nature of corruption crimes in the housing sector. It is noted that the majority of crimes in the housing and communal sector are stable corruption and are committed by officials, as well as by persons performing organizational, administrative and administrative functions at the enterprises of housing and communal services. The criminals have adapted to the new system of functioning of the housing and communal services and forms of control over its activities. They began to more often involve enterprise accountants, relatives and other close persons in their criminal schemes, thereby forming a stable criminal group in which all roles are carefully distributed and thought out. The Author analyzes judicial practice in corruption-related cases in the field of housing and communal services. The most typical ways of committing crimes in this area are shown. Attention is paid to violations related to the resettlement of citizens from hazardous housing. The issue of the organization of natural monopoly in our country, which reduce the effectiveness of the existing measures of state control and which directly affect the growth of corruption crimes, is investigated. Attention is focused on the deliberate obfuscation of the property rights of resource-supplying organizations and the withdrawal of income to offshore zones. The factors that contribute to the growth of corruption crimes in this industry are noted. On the basis of the study, the author concludes that the social danger of corruption crimes in the sphere of housing and communal services is conditioned by a high level of organization, selfish involvement of officials in the redistribution of funds in their favor, as well as the intricacy of schemes and methods of withdrawing funds from enterprises of housing and communal services.